Research of urban agglomerations from the position of a synergetic approach - Kravchenko, Kateryna (Human Geography Journal, 2024)
The article examines urban agglomerations as complex subsystems of the socio-geosystem, characterized by a set of synergetic properties: openness, dynamism, flexibility, hierarchy, and emergence, among others. Urban agglomerations evolve over time and change under the influence of internal and external factors. Their development is determined by various components, such as population dynamics, economic clusters, infrastructure development, investment, and innovation. The article emphasizes the necessity of a synergetic approach to research, which considers nonlinear interactions and emergent properties arising from complex systemic interconnections.One of the key stages in the evolution of an urban agglomeration is the study of decision-making points in the development trajectory, or bifurcation points, where urban agglomerations can transform in different directions depending on demographic, economic, or technological changes. The study identifies numerous challenges faced by urban agglomerations, including social inequality, overburdened urban infrastructure due to excessive urbanization, and more.The article describes three potentially possible scenarios for the development of urban agglomerations: sustainable development, conservation, and critical condition. Each scenario is determined by different levels of sensitivity and adaptation strategies in response to challenges arising in the context of urban agglomeration evolution.The application of the synergetic approach in the study of urban agglomerations has been tested using self-organizing Kohonen maps and cluster analysis to examine the most dynamically developing urban agglomerations in Asia. Based on available data, nine clusters of Asian countries with similar urbanization trends have been identified, along with their respective challenges and development prospects. The conducted analysis of urbanization processes in Asian urban agglomerations highlights relevant globalization challenges that are expected to become pressing for many urban agglomerations worldwide.Thus, ensuring the transition of urban agglomerations toward sustainable development requires an understanding of their complexity and synergetic nature, as well as the characteristics of transformation processes influenced by various factors.